Karakterisasi dan Formulasi Nanopartikel Ekstrak Tanaman Bundung (Actinoscirpus grossus) dengan Variasi Konsentrasi Basis Kitosan dan Na-TPP Menggunakan Metode Gelasi Ionik: Characterization and Formulation of Nanoparticles Extract of Bundung Plant (Actinoscirpus grossus) with Variations in Concentration of Chitosan and Na-TPP Bases Using the Ionic Gelation Method - Yuditha Mutia Windy; Khaliza Natasya Dilla; Jesika Claudia; Noval Noval; Ali Rakhman Hakim (Jurnal Surya Medika (JSM), 2022)
Bundung plant extract contains flavonoid secondary metabolite compounds that have the potential to kill Staphylococcus aureus bacteria and inhibit the fungus Candida albicans. Its utilization uses nanoparticle technology because the ability to penetrate cell walls can be penetrated by the size of colloidal particles. Nanoparticles are technologies that have a size of 10-1000 nm. The formation of nanoparticles using chitosan polymer and Na-TPP can produce preparations with good stability. This study aims to determine the characterization and formulation of nanoparticles and the effect of the concentration of chitosan and Na-TPP on the characterization of nanoparticles of plant extracts. This research is an experimental laboratory with a quasi-experimental design method and a one-group posttest-only research design. Bundung plant extracts formulated into nanoparticles with various concentrations of formula 1 (chitosan 0.1% and Na-TPP 0.2%), formula 2 (chitosan 0.15% and Na-TPP 0.15%), and formula 3 (chitosan 0.2% and Na-TPP 0.1%). Then organoleptic and characterization tests were carried out in particle size tests, zeta potential, and data were analyzed by ANOVA. All formulas showed nanoparticle size. The results of the nanoparticle characterization of the extract of the Bundung plant showed that F2 was the formula with the smallest particle size of 328.8 nm, but for the zeta potential value, the stable formula was F3 because it had a zeta potential value close to +/-30mV, i.e., 10.4mV. The statistical results of One Way ANOVA show that the significance value is <0.05, which means that there is an effect of variations in the concentration of chitosan and Na-TPP. Variations in the concentration of chitosan and Na-TPP in each formula can affect the particle size and zeta potential value.